Thermal denaturation and aggregation of hemoglobin of Glossoscolex paulistus in acid and neutral media - Carvalho, José Wilson P.; Carvalho, Francisco A.O.; Santiago, Patrícia S. [UNESP]; Tabak, Marcel (Elsevier, 2013)
The thermal denaturation and aggregation of the HbGp, in the oxy- and cyanomet-forms, was investigated by DSC, AUC, DLS, optical absorption and CD, in the pH range from 5.0 to 7.0. Oxy-HbGp has a denaturation process partially reversible and dependent on the temperature. DSC melting curve is characterized by a single peak with Tc value of 333.4±0.2K for oxy-HbGp, while two peaks with Tc values of 332.2±0.1 and 338.4±0.2K are observed for cyanomet-HbGp, at pH 7.0. In acidic pH oxy- and cyanomet-HbGp are more stable showing higher Tc values and aggregation. AUC data show that, HbGp, at pH 7.0, upon denaturation, remains undissociated at 323K, presenting oligomeric dissociation at 333 (12±3% of tetramer and 88±5% of whole HbGp) and 343K (70±5% of monomer and 30±2% of trimer). DLS data show that the lag period before aggregation is dependent on the temperature and HbGp concentration. Optical absorption and CD results show that the increase of temperature leads to the oxy-HbGp oxidation and aggregation, above 331K, in acidic pH. CD data, for HbGp, present a greater thermal stability in acid medium than at neutral pH, with similar Tc values for both oxidation forms. Our data are consistent with previous studies and represents an advance in understanding the thermal stability of oligomeric HbGp structure. © 2012 Elsevier B.V.
Keywords: AUC; Denaturation and aggregation; DLS; DSC; Extracellular hemoglobin; Glossoscolex paulistus; hemoglobin; oxyhemoglobin; absorption spectroscopy; acidity; circular dichroism; differential scanning calorimetry; dissociation; earthworm; hydrodynamics; light scattering; melting point; nonhuman; oxidation; pH; protein aggregation; protein denaturation; protein structure; temperature; thermostability; ultracentrifugation; Absorption; Acids; Animals; Calorimetry, Differential Scanning; Circular Dichroism; Enzyme Stability; Hemoglobins; Hydrodynamics; Hydrogen-Ion Concentration; Kinetics; Light; Molecular Weight; Oligochaeta; Optical Phenomena; Protein Denaturation; Protein Structure, Quaternary; Scattering, Radiation; Temperature; Ultracentrifugation; Glossoscolex